Influence of long-term episodic cyclic loading with rest periods on pipe-soil interaction - Zhechen, Hou; Fauzan, Sahdi; Christophe, Gaudin; Mark, Randolph (2022)
Steel catenary risers (SCRs) are pipelines widely used for transporting hydrocarbon resources from subsea fields to floating structures. The assessment of long-term fatigue life of SCRs, especially at the section close to the touchdown zone, where complex soil-fluid-structure interaction occurs, remains a significant challenge for designers. A key question that is currently causing debate is the evolution of the cyclic stiffness for riser-seabed interaction and the associated competing effects of soil remoulding with those of consolidation. The estimation of soil stiffness due to pipe movements is critical for fatigue assessment over the SCR operational life. This paper provides insights on soil hardening through reconsolidation, after initial cyclic soil remoulding. This was achieved by comparing the long-term soil stiffness evolution between a continuous cyclic test and episodic cyclic tests with intermittent rest periods. Test results show that soil stiffness recovers significantly due to soil consolidation during rest periods, but this recovery is less than that for a continuous cyclic test with the same elapsed test time. These results provide an improved understanding of pipe-soil interaction with rest periods during which consolidation occurs, and the subsequent influence on the longterm evolution of the cyclic stiffness.